2016
DOI: 10.1371/journal.pone.0166624
|View full text |Cite
|
Sign up to set email alerts
|

Seed Quality Traits Can Be Predicted with High Accuracy in Brassica napus Using Genomic Data

Abstract: Improving seed oil yield and quality are central targets in rapeseed (Brassica napus) breeding. The primary goal of our study was to examine and compare the potential and the limits of marker-assisted selection and genome-wide prediction of six important seed quality traits of B. napus. Our study is based on a bi-parental population comprising 202 doubled haploid lines and a diverse validation set including 117 B. napus inbred lines derived from interspecific crosses between B. rapa and B. carinata. We used ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 81 publications
(99 reference statements)
1
16
1
Order By: Relevance
“…The seed-quality traits had high heritability and accuracies ranging from 0.38 to 0.56. These values were lower than reported previously (Jan et al 2016;Zou et al 2016); however, this can be explained by the larger training population sizes utilised in those studies. Würschum et al (2014) reported on prediction accuracies within DH families consisting of few individuals and reported accuracies similar to, or slightly lower than, the results reported here.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…The seed-quality traits had high heritability and accuracies ranging from 0.38 to 0.56. These values were lower than reported previously (Jan et al 2016;Zou et al 2016); however, this can be explained by the larger training population sizes utilised in those studies. Würschum et al (2014) reported on prediction accuracies within DH families consisting of few individuals and reported accuracies similar to, or slightly lower than, the results reported here.…”
Section: Discussioncontrasting
confidence: 75%
“…In maize, WGP has been more effective for improving grain yield under drought stress than phenotypic selection alone (Vivek et al 2017). WGP has been applied to B. napus doubled-haploid (DH) populations for yield and quality traits with varying degrees of success, depending on the population structure, number of individuals within the population, marker density and trait heritability (Würschum et al 2014;Zou et al 2016). With respect to heat stress, Bita and Gerats (2013) discuss the difficulty in using low-effect QTLs for improving quantitative traits such as tolerance to increased temperatures and suggest WGP as a promising alternative.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, in Brassica napus breeding, traits related to commercial success are of highest importance (Friedt and Snowdon 2010). For this reason rapeseed breeding strategies are oriented on developnig new cultivars with high oil, protein as well as low erucic acid, glucosinolate and fiber content (Möllers 2004;Abbadi and Leckband 2011;Zou et al 2016;Körber et al 2016). For this purpose knowledge of genetic diversity is indispensible in the development of commercial cultivars (Ahmad et al 2013;Liu et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The markers showing the same segregation pattern were classified into the same genetic bins, and one of the markers with the highest quality were choose to construct genetic map using JoinMap 4.0 (Van Ooijen, 2006). Double crosses and recombination frequency were checked by Mapdisto 2.0 (Lorieux, 2012;Zou et al, 2014;Zou et al, 2016).…”
Section: Mapping Populations and Genetic Map Constructionmentioning
confidence: 99%